MOTIVASI KERJA GURU HONORER DITINJAU DARI QUALITY OF WORK LIFE - HERWINDO HARIWIBOWO; IRMA ROSALINDA; ADE SHABRINA KHAIR (Journal of Research and Measurement in Psychology, 2015)
Motivation work temporary teachers are needed in education. With a high work motivation is expected teachers will have quality in transferring knowledge to learners. One study to measure work motivation is related to quality of work life. This study aims whether there is influence of quality of work life on the motivation of teachers work honorary. Researcher used scale quantitative methods psychology. Researcher used adapted instrument, namely Motivation Teacher Work and Quality of Work Life Scale. There are 100 samples of respondent which is the teacher. The data processing used in the testing of hypothesis analytics regression linears. Result F count equal to 49,343 bigger than F table hence alternative hypothesis accepted. The resulting influence is positive, meaning the higher quality of work life the higher the motivation of the teacher work honorary. The effect of quality of work life on work motivation is 33.5% and the rest is influenced by other factors.